Mosaic frequency selective surface absorber for low profile directive antenna application - Mohamed Nafis, Nur Biha; Himdi, Mohamed; A Rahim, Mohamad Kamal; Tamchek, Nizam; Osman, Nurul Huda; Abd Rahman, Mohd Amiruddin (Institute of Electrical and Electronics Engineers, 2024)
This study investigated the incorporation of the Mosaic Frequency Selective Surface (MFSS) absorber at a separation distance (d) lower than quarter-wavelength from a basic monopole antenna (MA), to augment the MA’s directivity, thereby increasing the front-to-back ratio (FBR). The resistive MFSS is backed with a metal conductor, with 5 mm air gap spacing in between, to act as MFSS absorber. For the MA, a subminiature version A (SMA) connector is attached at the middle bottom of the silver conductor ground plane. The simulation process is conducted using the Computer Simulation Technology (CST) Microwave Studio software. By comparing simulated result performances between MA, perfect electric conductor incorporated monopole antenna (PECMA), and MFSS absorber incorporated with monopole antenna (MFSSAMA), the MFSSAMA demonstrated promising performance, in which FBR of 15.16 dB is obtained when d is only 4 mm (0.08 λfr). Even though the PECMA demonstrated the highest FBR of 17.79 dB, however, PECMA experienced impedance mismatched when d = 4 mm. Meanwhile, the MA exhibited zero FBR. This had proven the significant suitability of the MFSS absorber incorporated with MA for low-profile directive antenna applications.